2019
DOI: 10.1016/j.molmet.2019.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Informing β-cell regeneration strategies using studies of heterogeneity

Abstract: BackgroundCurrent therapeutic strategies for type 1 (T1DM) and type 2 diabetes mellitus (T2DM) rely on increasing or substituting endogenous insulin secretion in combination with lifestyle changes. β-cell regeneration, a process whereby new β-cells arise from progenitors, self-renewal or transdifferentiation, has the potential to become a viable route to insulin self-sufficiency. Current regeneration strategies capture many of the transcriptomic and protein features of native β-cells, generating cells capable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 119 publications
(188 reference statements)
0
9
0
Order By: Relevance
“…A detailed discussion of the abovementioned strategies for increasing the beta cell population is beyond the scope of this review and can be found elsewhere (Basile et al, 2019;Nasteska et al, 2019;Tan et al, 2019;Guney et al, 2020;Helman and Melton, 2021). Here, we summarize and discuss recent advances in the field of human beta cell proliferation, focusing more closely on the contributions of mitogen synergy and transcriptomics to elucidating the signaling pathways and genes involved in beta cell proliferation, providing hints for the discovery of novel mitogens.…”
Section: Strategies For Replenishing Beta Cell Massmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed discussion of the abovementioned strategies for increasing the beta cell population is beyond the scope of this review and can be found elsewhere (Basile et al, 2019;Nasteska et al, 2019;Tan et al, 2019;Guney et al, 2020;Helman and Melton, 2021). Here, we summarize and discuss recent advances in the field of human beta cell proliferation, focusing more closely on the contributions of mitogen synergy and transcriptomics to elucidating the signaling pathways and genes involved in beta cell proliferation, providing hints for the discovery of novel mitogens.…”
Section: Strategies For Replenishing Beta Cell Massmentioning
confidence: 99%
“…Thus, theoretically, the targeted expansion of a proliferating beta cell subpopulation may lead to enrichment in proliferation-prone but physiologically suboptimal subtypes with low levels of insulin synthesis and secretion. Hence, obtaining the right balance between the various types of beta cells appears to be crucial (Nasteska et al, 2019). However, it remains feasible that a population of proliferationcompetent beta cells would eventually diversify into beta cell subtypes, under the direction of growth factors in vitro or endogenous cues in vivo.…”
Section: Proliferating Subpopulations Of Beta Cellsmentioning
confidence: 99%
“…The prevalence of DM has increased dramatically in recent decades and is projected to rise to 642 million people by 2040 ( 1 ), with profound impacts on quality of life, demands for health services, and economic costs ( 2 ). There are two common syndromes, type 1 (T1D) and type 2 diabetes (T2D), characterized by an absolute or relative deficiency of β-cells, respectively ( 3 ). A previously held belief stipulated that the fate of fully differentiated β-cells is fixed and that gradual β-cell death due to glucotoxicity was a final outcome of DM ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nkx6.1 thus controls the expression of genes that are not essential for acute insulin secretion, the function of which can be compensated for. Considerations that Nkx6.1 deficiency is an ultimate determinant of β-cell pathology beyond cell trans-(de-)differentiation or β-cell identity are not supported by our results.Recent advances in studies of the etiology of type 2 diabetes focus on a consensus, pointing out to the "altered β-cell identity" as a concept describing processes in type 2 diabetes development in humans 1 , in contrast to concepts 2 of pancreatic β-cell de-differentiation and/or trans-differentiation, which were previously considered to be essential causes [1][2][3][4][5][6][7][8][9][10] . The maintained β-cell identity allows an altered transcriptome and metabolome, but only when the main minimum functional features of pancreatic β-cells are conserved.…”
mentioning
confidence: 99%
“…The maintained β-cell identity allows an altered transcriptome and metabolome, but only when the main minimum functional features of pancreatic β-cells are conserved. The precise number and nature of these minimum features is currently unknown.Pancreatic β-cell dedifferentiation denotes a regression toward an earlier progenitor state with a stem-celllike phenotype, whereas transdifferentiation means a change into other islets cell types, mostly to α-cells or δ-cells [1][2][3][4][5][6][7][8][9][10] . Progress in our understanding of the transcription factors controlling rodent embryonic development of the pancreatic epithelium and commitment to β-cell lineage identified several transcription factors as "β-cellspecifying" 11,12 , such as Nkx6.1, Nkx2.2, Pdx1, FoxA2, Six2 and Six3.Nkx6.1 is a homeobox-containing transcription factor 13 , with increased expression in the trunk area of the pancreatic epithelium from mouse embryonic days 9.5 to 13 (E9.5 to E13), and it determines the later endocrine lineage 12 .…”
mentioning
confidence: 99%